Representación e historiografía en México 1930-1950. "Lo mexicano" ante la propia mirada y la extranjera - Pérez Montfort, Ricardo (El Colegio de México, A.C., 2013)
This paper examines the transformations experienced by Mexican historiography during the 20th century, from the 1930's to the 1950's. From being an ideologized history -that created nationalist “revolutionary” consciences and identities-, it turned into a history with more scientific and cultural claims, in the midst of different political, economic, social and, especially, cultural adjustments. Within the international context, changes in approaches and methodologies took place amid the economic and political rearrangement brought about by World War II and its first consequences. Both Mexico and the United States, as well as most European countries, experienced a “change of direction” that undoubtedly affected Mexicanist historical interpretations, asserting some of them, while discarding others.